VALUE OF LIMFOSIT AND MONOSIT OF BALI CATTLE BASED ON ORGANIC MAINTAIN - Parmayoga, I Putu Indra; Suwiti, Ni Ketut; Suartha, I Nyoman (Buletin Veteriner Udayana, 2020)
Bali cattle are maintained in various ways, namely intensive, semi-intensive (simantri) systems, conventional and organic based maintenance. Organic based means that Bali cattle are fed with food from their environment without chemical additives such as minerals, vitamins, medicines, vaccines, supplements, and other addictive substances. This study aims to look at the value of Bali cattle lymphocytes and monocytes that are maintained on an organic basis. Samples in the form of whole blood were taken through the jugular vein and hematological examination was performed using the Veterinary Hematology Analyzer. The results of the study produced a mean total lymphocytes and monocytes 3,77 x /?l dan 0,53 x /?l. The average value of bali lymphocytes and monocytes that are maintained on an organic basis are still in the range of normal values.